ANALISIS PEMBIBITAN OLAHRAGA BERBAKAT BOLAVOLI SDIOARJO JAYA KABUPATEN SIDOARJO - AHSANUL RIZKY, MUKHTAR (Jurnal Kesehatan Olahraga, 2016)
The achievement of a sport achievement is based on good sport coaching; the peak is closely related to human resources, infrastructure, and the training programs. Sidoarjo Victorious is a volleyball coaching program which is owned by the government of Youth, Sport, Culture, and Tourism which was established in early 2012 and aims to boost achievement in the field of sports, especially volleyball. Formulation of this research is how the coaching of volleyball in Sidoarjo Victorious Sidoarjo city and has a goal to find out the results of the volleyball coaching in Sidoarjo Victorious Sidoarjo city. This research used the method of quantitative descriptive research. In addition, the method used is SWOT (strength, weakness, opportunity, threat). By using the SWOT method, it is expected to get optimal results in observing the volleyball coaching of Sidoarjo Victorious Sidoarjo Regency. Furthermore, the type of instrument used is questionnaire. The results of this study can be seen that the volleyball coaching in Sidoarjo Jaya is very good, that is 93,62 %. That number was obtained from the questionnaire completed by athletes, coaches and administrators of volleyball coaching Sidoarjo Victorious in terms of human resource with average of 89%, infrastructure 96.33%, and exercise program 95,55%. Some trainers have already had a coaching license, and there are also good communication between administrators, coaches, and athletes. The facilities and infrastructure in the volleyball coaching Sidoarjo Victorious is sufficient to implement guidance and training. In addition, the training program that was created in volleyball coaching of Sidoarjo Victorious is also good. There are daily, weekly, monthly, and yearly exercise programs; moreover, there will always be an evaluation after carrying out training or competition. Keywords: coaching, volleyball, Sidoarjo Victorious, Sidoarjo City, SWOT